Cultures in conflict : Christians, Muslims, and Jews in the age of discovery - Lewis, Bernard, 1916- (New York : Oxford University Press, 1995)
With elegance and erudition, Lewis explores that climactic year of 1492 as a clash of civilizations - a clash not only of the New World and the Old but also of Christendom, Islam, and the Jews. In the same year that Columbus set sail across the Atlantic, he reminds us, the Spanish monarchs captured Granada, the last Muslim stronghold on the peninsula, and also expelled the Jews. Lewis uses these three epochal events to explore the nature of the expansion of Europe, placing the voyages of discovery in a striking new context. He traces Christian Europe's path from primitive backwater on the edges of the vast cosmopolitan Caliphate, through the heightening rivalry of Christianity and Islam, to the triumph of the West, examining the factors behind their changing fortunes. That contest long remained more important in many Christians minds than the New World: as late as 1683, Vienna almost fell to the Ottoman armies. Lewis also reflects on changing qualities in European and Islamic cultures and the place of the Jews in both. The Jews who fled Spain found a receptive environment in Turkey; but the balance of tolerance and openness to innovation steadily shifted west. The voyages of discovery were themselves a part of the Christian-Muslim conflict, he writes, an attempt to outflank the Islamic world. The European explorers sailed into a world they scarcely understood; and yet they imposed their own perceptions of geography on the lands they conquered. Africa, Asia, the Middle and Far East, the Old and New Worlds - as intellectual concepts, all are European creations, Lewis observes; ironically, these same definitions have been accepted by even the most anti-Western activists.
Based on the Merle Curti lectures delivered at the University of Wisconsin, Madison, May 1993.
Includes bibliographical references (p. [83]-94) and index.
Keywords: Europe -- History -- 1492-1517.; Europe -- History -- 15th century; Europe -- Territorial expansion; Jews -- History -- 70-1789.; Islamic Empire -- History -- 1258-1517.; Europa -- Historia -- Siglo XV; Europa -- Historia -- 1492-1517.; Europe -- Histoire -- 1492-1517.; Europe -- Histoire -- 15e siáecle.; Europe -- Expansion territoriale; Empire islamique -- Histoire -- 1258-1517.; Juifs -- Histoire -- 70-1789.